Transposition of EU legislation in Italy - Molnár, Anna (Acta Scientiarum Socialium, 2011)
The aim of this paper is to provide an overview of the process of Europeanization on the national level. As a consequence of the governmental reÂ¬forms (2005–2006) in Italy, the Europeanization process has taken shape. In this framework the impact of the institutional system and the decision-making processes within European Integration can be justified beyond doubt in the national and sub-national institutions of the Italian political system. The case of Italy shows that the integration had unambiguous effects on the national, regional, and local levels of decision-making, on coordination and governmental structures, actors, tasks, authorities, and competences, in accordance with the principles of multilevel governance. Both the increasingly frequent problems of the economic structure and the decrease in confidence in the Union and its institutions have recently brought the EU-coordination’s deficiencies to the surface and have strengthened the need for reforms.